A Systematic Review of Teaching Strategies for Incorporating Indigenous Knowledge Systems in Physical Education - Rishabh Aswal (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The abstract of this research paper highlights a methodological review of different teaching strategies aimed at incorporating Indigenous Knowledge Systems (IKS) into physical education. The study emphasizes how integrating Indigenous cultures, traditional sports, and physical activities can enhance students’ learning experiences. Indigenous Knowledge Systems refer to the unique, traditional, and community-based knowledge developed over generations within Indigenous communities. These knowledge systems include traditional games, rituals, and movement practices that hold cultural and educational significance. By integrating these elements into physical education, educators can offer students a more holistic and culturally relevant learning experience. The research aims to identify effective teaching strategies that not only preserve Indigenous heritage but also improve students’ engagement and participation in physical education. The inclusion of IKS can lead to greater cultural awareness, allowing students to understand and appreciate diverse traditions. Additionally, it promotes equity in education by acknowledging and valuing Indigenous contributions, ensuring a more inclusive curriculum. The study employs a systematic review approach to analyze existing literature, policies, and educational models that have successfully incorporated IKS into physical education. Through this review, the research seeks to determine the most effective strategies that enhance student learning outcomes while maintaining cultural authenticity. This research advocates for a more inclusive and effective education system that embraces Indigenous traditions. By integrating IKS into physical education, educators can create meaningful, contextually relevant learning experiences that benefit students both academically and culturally.